D-glucaro-1,4-lactone alleviates acetaminophen-induced hepatotoxicity in mice via modulating gut microbiota and metabolites associated with Lactobacillus–glutamine and nicotinic acid pathways - Song, Zhiying; Pan, Yiran; Wang, Zeyu; Chen, Yujing; Deng, Yufeng; Wang, Lele; Hu, Qi; Huang, Wenxiang; Sun, Shuilin; Xie, Baogang (Frontiers in Pharmacology, 2025)
ObjectiveThis study investigated the hepatoprotective effect and underlying mechanisms of D-glucaro-1,4-lactone (1,4-GL), a natural compound found in fruits and vegetables, against acetaminophen (APAP)-induced acute liver injury (ALI) in mice, which had not been previously explored.MethodsA stable ALI model was established in male C57BL/6J mice using 300 mg/kg APAP after fasting. Mice were pretreated orally with glutathione (200 mg/kg), or 1,4-GL (100 mg/kg or 200 mg/kg) for five consecutive days before APAP challenge. Serum biochemical markers were measured. Liver histopathology was assessed via H&E staining. Gut microbiota composition was analyzed using 16S rRNA sequencing of fecal samples. Liver metabolites were profiled using 1HNMR metabolomics.Results1,4-GL pretreatment (especially 200 mg/kg) significantly ameliorated APAP-induced liver damage: it reduced serum ALT, AST, TBIL, and MDA levels (P < 0.05), increased GSH and SOD levels (P < 0.05), and attenuated hepatic necrosis and inflammation. 1,4-GL increased the abundance of the beneficial gut bacterium Lactobacillus (significantly reduced by APAP) and elevated hepatic levels of protective metabolites isoleucine, glutamine, and nicotinic acid. Correlation analyses between gut microbiota and liver metabolites revealed that glutamine and nicotinic acid were significantly positively correlated with Firmicutes and Lactobacillus, while showing a significant negative correlation with Lachnoclostridium. Lactobacillus was identified as a key beneficial bacterium, whereas Lachnoclostridium was associated with increased disease severity.Conclusion1,4-GL exerts a beneficial regulatory effect on APAP-induced ALI by the Lactobacillus-glutamine/nicotinic acid pathway, highlighting its potential as a therapeutic agent for drug-induced liver injury.